Using technology for patient-centered care at home after CAR T-cell therapy or stem cell transplant: a prospective feasibility study - Moore, Susan L.; Peterson, Glen J.; Montoya, Sarah R.; Conte, Bellinda K.; Brahler, Rachel K.; Hutchison, Carolyn; Hoople, Katherine L.; Smith, Clayton A. (Frontiers in Immunology, 2025)
IntroductionFebrile neutropenia, neurotoxicity, and cytokine release syndrome are dangerous and damaging side effects seen in more than half of patients with cancer who receive critical chemotherapies or immunotherapies respectively. Early intervention and care can reduce complications, but timely treatment in the outpatient setting is often delayed due to dependency on interval-based, patient-driven self-assessments. Using digital health technologies (DHT) to monitor patients remotely can improve time-to-intervention and health outcomes. Providing follow-up treatment and essential support to patients at home can further reduce patients’ and caregivers’ burden and improve patient satisfaction.MethodsThis pilot feasibility study examined the results of a patient-centered program for technology-assisted remote patient monitoring and symptom reporting for patients undergoing autologous or allogeneic stem cell transplant (SCT) or CAR T-cell therapy. Technical and operational feasibility and user experience were assessed for patients, caregivers, and providers. Ten patients between 30 and 80 years old participated in the study for up to 30 days after CAR T-cell therapy or autologous SCT or up to 90 days after allogeneic SCT. Patients wore biometric sensors around the clock to monitor vital signs and engaged with a chatbot through bidirectional SMS text messages for symptom reporting and regular health check-ins. Virtual care center personnel monitored patient status and followed up with patients or their care providers as needed. Patients, caregivers, and providers completed surveys about their program experience; patients also completed brief interviews.ResultsNine of 10 patients engaged with DHT based monitoring as intended. A total of 219 alerts were generated, 171 from wearables and 48 from the chatbot and check-ins. Fifty-seven alerts required follow-up with patients, 26 required care team follow-up, and 10 required patients to be seen in a clinical setting. Users found the program acceptable overall, with patients and caregivers reporting perceptions of being more cared for and providers feeling that it improved quality of care. Suggestions received included a desire for more information and improved communication and alerting processes.DiscussionOverall, DHT-based remote patient monitoring was feasible for use with patients receiving SCT and CAR T-cell therapy. Effective practice integration requires adaptation to clinical workflows. Further evaluation of patient acceptance over time and effectiveness at improving health outcomes is recommended.